IBLI—opening up new frontiers for pastoralists in northern Kenya - International Livestock Research Institute (International Livestock Research Institute, 2014)
Opening up new frontiers for Pastoralists in Northern Kenya. Wajir Index Based Livestock Takaful (IBLT) payout ceremony, March 2014.